KEBIJAKAN HUKUM PIDANA DALAM UPAYA PENANGGULANGAN MALPRAKTIK PROFESI MEDIS - Bambang Tri Bawono (Unissula, 2011)
Criminal law policy in essence an attempt to create criminal legislation to fit the circumstances at a certain time (ius constitutum) and future (ius constituendum). Efforts to prevent and control crime is not just law enforcement duties, but also the task forces of law-making (legislative), even this legislative policy is the most strategic stages of the penal policy, therefore, faults / weaknesses of the legislative policy is a strategic mistake that a barrier to prevention efforts and crime prevention at this stage of the application and execution.From the results of this study concluded that the positive criminal law in Indonesia about the malpractices continue to show weakness in mitigation policy and shows also that the uniform criminal laws in the medical field is not working properly (Wetboek van Strafrecht, Health Regulations). As a parent rule of criminal law, Code number 29 of 2004 on the legal practice of Medicine as a primary rule in the medical field to come up with emphasis on uniformity and consistency in the formulation of crime, the right and responsibility for the crime so as to provide a sense of justice for victims and can be a deterrent effect and also the use of penal mediation as a regional medical crime constituendum ius in an effort to provide justice for those who become victims of crime in the medical field. This is related to the development of criminal law in many countries today, which is using the law of mediation as an alternative to solve the problems in the field of criminal law.Keyword : Medical Law Policy, Medical Profession